Superior vena cava syndrome secondary to recurrent coronary artery fistula: A case report and literature review. Issue 51 (December 2017) - Chen, Peng-fei; Tang, Liang; Liu, Zhen-zhen; Hu, Xinqun
Abstract: Rationale: Coronary artery fistula (CAF) is characterized by an abnormal communication of a coronary artery with a cardiac chamber or a great vessel bypassing the capillary bed. Surgical closure of large or symptomatic CAF is the gold standard treatment. However the previously closed CAF still has the possibility to reopen. Superior vena cava syndrome (SVCS) is defined as a condition that occurs when the obstruction of the superior vena cava interrupts blood flow from the head, upper extremities, and thorax to the right atrium and can present a life-threatening situation. In this report, we described a case of SVCS, which was secondary to the compression by a huge aneurysm formed in a recurrent CAF, as a long-term complication associated with surgical treatment of CAF. Patient concerns: A 47-year-old woman presented with chief complaint of progressive exertional dyspnea for one month. Diagnoses: Superior vena cava syndrome and recurrent coronary artery fistula. Interventions: Reoperation for ligation of the fistulous and excision of the aneurysm were performed. Outcomes: The patient made an uneventful recovery and her postoperative course through 1-year follow-up was uneventful. Lessons: First, SVCS is a rare but clinically important postoperative complication of surgical ligation of CAF. Second, surgical ligation of the fistula alone is unlikely to prevent the ectatic course. Therefore, long-term follow-up is mandatory for patients with CAF undergoing surgical closure.